Corneal Perforation during Combination Chemotherapy including Cetuximab in a Patient with a History of Herpetic Keratitis - Keiichi Aomatsu; Koji Sugioka; Aya Kodama-Takahashi; Masahiko Fukuda; Hiroshi Mishima; Shunji Kusaka (Case Reports in Oncological Medicine)
Purpose. To report a case of corneal perforation, in a patient with a history of herpetic keratitis, during combination chemotherapy including cetuximab. Case. We report the case of a 71-year-old man who was diagnosed with a hypopharyngeal carcinoma and received radiation therapy combined with cetuximab, the epidermal growth factor receptor (EGFR) inhibitor monoclonal antibody. He was referred to us because of ocular hyperemia and corneal perforation in his left eye. In spite of conservative therapy, his corneal perforation was exacerbated, with iris incarceration into the wound site and exposure to the surface of the cornea. He therefore discontinued treatment with the combination chemotherapy and underwent lamellar keratoplasty using a preserved donor cornea. After treatment with cetuximab resumed, there was no recurrence of the corneal perforation. Conclusion. We have presented the first case of cetuximab-related corneal perforation in a patient who had a history of recurrent herpetic keratitis. EGFR inhibitors, such as cetuximab, can induce corneal perforation in cases with a history of herpetic stromal keratitis.